A systematic review and meta-analysis of clinical and functional outcomes of artificial urinary sphincter implantation in women with stress urinary incontinence. Issue 2 (2nd April 2020) - Barakat, Bara; Franke, Knut; Hijazi, Sameh; Schakaki, Samer; Gauger, Ulrich; Hasselhof, Viktoria; Vögeli, Thomas-Alexander
ABSTRACT: Objective: To evaluate the complications and results of artificial urinary sphincter (AUS) implantation in women with stress urinary incontinence (SUI). Methods: A selective database search using keywords (1990–2019) was conducted to validate the effectiveness of the AUS in women. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were utilised. The meta-analysis included 964 women (15 studies) with persistent SUI. The Newcastle-Ottawa score was used to determine the quality of the evidence in each study. The success rate and complications associated with the AUS were analysed. Results: Meta-analysis of the published studies showed that complete continence was achieved at a mean rate of 79.6% (95% confidence interval [CI] 72.2–86.6%) and a significant improvement was achieved in 15% (95% CI 10–25%). The mean (range) follow-up was 22 (6–204) months. The mean number of patients per study was 68. The mean (range) explantation rate was 13 (0–44)%. Vaginal erosion occurred in a mean (range) of 9 (0–27)% and mechanical complications in 13 (0–47)%. Infections accounted for 7% of the complications. The total mean (range) revision rate of the implanted AUS was 15.42 (0–44)%. The mean (range) size of the cuff used was 6.7 (5–10) cm. Conclusion: Our present analysis showed that implantation of an AUS in women with severe UI is an effective treatment option after failure of first-line therapy. However, the currently available study population is too small to draw firm conclusions. Abbreviations: AMS: American Medical Systems; AUS: artificial urinary sphincter; EAU: European Association of Urology; LE: Level of Evidence; PRISMA: Preferred Reporting Items for Systematic Reviews and Meta-Analyses; QoL: quality of life; SHELTER: Services and Health for Elderly in Long TERm care (study); SUI: (stress) urinary incontinence